A possible initiation mechanism of Muztag rock avalanche induced by nearby fault creep - Zhang, Yingbin; Wang, Qingdong; Yu, Pengcheng; Wang, Lei; Zhang, Zhongkun; He, Jianxian; Xiao, Yao; Peng, Xinyan; Wang, Wenfang; Cheng, Qiangong; Bohnhoff, Marco (Earth surface processes and landforms, 2025)
Rock avalanches are catastrophic events that can be triggered by various geological and climatic factors. Large‐scale rock avalanches have been observed near fault zones, indicating a potential relationship between fault creep motions and the initiation of rock avalanches. This study proposes a physical mechanism that explains how fault creep leads to the initiation of near‐fault rock avalanches through stress redistribution. The Muztag rock avalanche which occurred near the Muztag fault in Muztag Ata, Kashgar, China is revisited using field measurements and numerical modelling. We consider the Muztag rock avalanche model with its initial slope toe supported by a portion of the fault's hanging wall. Site‐specific numerical simulations using discontinuous deformation analysis (DDA) reveal that fault creep initially generates localized stress concentrations at the slope toe. Once the slope toe completely detaches from the hanging wall, the slope toe fails when the accumulated stress exceeds the local strength, resulting in a sharp stress drop. This stress redistribution triggers consecutive failure at the bottom of the rear edge and middle slope, forming a through‐going shear sliding surface, which leads to the initiation of the overall rock avalanche. The kinematic processes of the avalanche, including sliding distance and deposit thickness, as modelled by DDA, are consistent with the post‐failure characteristics of the Muztag rock avalanche. These findings suggest that tectonic fault creep motions can play a significant role in inducing near‐fault rock avalanches. Schematic diagram of rock avalanche caused by fault creep. Cracking (failure) at slope toe caused by stress concentration upon the detachment of slope toe from the hanging wall.